The Impact of Indigenous Religious Practices on the Art of Dompim No.1 - Boakye-Yiadom, Fredrick (2011)
A Thesis submitted to the school of Graduates Studies of Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements of the award of the degree in Master of Arts in African Art and Culture